Bio-inspired coating strategies for the immobilization of polymyxins to generate contact-killing surfaces - Alves, Diana Filipa Barros (2016)
Microbial colonization of indwelling devices remains a major concern in modern healthcare. Developing approaches to prevent biomaterial-associated infections (BAI) is, therefore, in great demand. This study aimed to immobilize two antimicrobial peptides (polymyxins B and E) onto polydimethylsiloxane (PDMS) using two polydopamine (pDA)-based approaches: the conventional two-step method involving the deposition of a pDA layer to which biomolecules are immobilized, and a one-step method where peptides are dissolved together with dopamine before its polymerization. Surface characterization confirms the immobilization of polymyxins onto PDMS at a non-toxic concentration. Immobilization of polymyxins using a one-step pDA-based approach is able to prevent Pseudomonas aeruginosa adhesion and kill a significant fraction of the adherent ones. Living cells adhered to these modified surfaces exhibit the same susceptibility pattern as cells adhered to unmodified surfaces, highlighting no resistance development. Results suggest that polymyxins immobilization holds a great potential as an additional antimicrobial functionality in the design of biomaterials.